2008
DOI: 10.1002/jclp.20455
|View full text |Cite
|
Sign up to set email alerts
|

Do current beliefs predict hypomanic symptoms beyond personality style? Factor analysis of the hypomanic attitudes and positive predictions inventory (HAPPI) and its association with hypomanic symptoms in a student population

Abstract: A self-report scale called the Hypomanic Attitudes and Positive Predictions Inventory (HAPPI) has been developed to assess cognitions that distinguish between bipolar disorder and nonclinical controls (Mansell, 2006; Mansell & Jones, 2006). We recruited 191 undergraduate students to assess the associations between the HAPPI and self-reported past (MDQ; Hirschfeld et al., 2000) and present (ISS; Bauer et al., 1991) bipolar symptoms, and to explore the factor structure of the scale. The HAPPI correlated with pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
45
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 44 publications
7
45
1
Order By: Relevance
“…In addition, HYP was a unique predictor of ISS Activation, but not Conflict or Depression. This is consistent with previous studies (e.g., Mansell et al 2008).…”
Section: Internal Statessupporting
confidence: 94%
See 3 more Smart Citations
“…In addition, HYP was a unique predictor of ISS Activation, but not Conflict or Depression. This is consistent with previous studies (e.g., Mansell et al 2008).…”
Section: Internal Statessupporting
confidence: 94%
“…The results suggest that beliefs measured by the HAPPI are independent yet also complement other trait measures, which have previously been shown to be predictive of both analogue and clinical bipolar symptoms (Kwapil et al 2000;Meyer et al 1999Meyer et al , 2001. It has already been demonstrated (Mansell et al 2008) that the 50-item HAPPI was uniquely associated with a history of hypomanic experiences. That the expanded version is independently related to subsequent hypomania-relevant internal states (ISS Activation and Conflict) is encouraging.…”
Section: Internal Statesmentioning
confidence: 91%
See 2 more Smart Citations
“…Recent factor-analytic evidence suggests that these three facets of state-dependent cognition are independent and that each adds unique variance to hypomanic risk (Johnson & Jones, in press). , Mansell Rigby, Tai, and Lowe (2008) recently found that hypomanic symptoms were correlated with the tendency to endorse a broad range of cognitive statements, including statements regarding consequences of the positive moods (e.g., not being responsible for dealing with the moods, not being understood, not eating), loss of control over moods, diminished tearfulness (when I feel excited, my fears and worries are no longer real), and response styles to positive moods (mood-related increases in idea generation). Indeed, one recent focus has been on understanding the cognitive processes involved in the manic ascent, and to provide interventions tailored toward these issues (Mansell & Pedley, 2008).…”
mentioning
confidence: 99%